Reflections on forty years of education in Spain, or the irresistible attraction of laws - Puelles Benítez, Manuel (Historia y Memoria de la Educación, 2015)
In almost forty years of democracy, educational policy in Spain has given rise to a phenomenon that has produced effects quite the opposite from those that were sought, with an excess of educational laws resulting in remarkable and constant legislative instability. This paper analyses the underlying reasons for this phenomenon, particularly the policies of the two major national parties and the embodiment in education laws of their systemic models of education, models which clearly bear the stamp of their respective ideologies. This has inevitably led to legislative reforms when the electorate has voted for a change of government. This analysis points to the need for a new consensus on education to ensure the effective implementation of the reforms launched by these laws.